1999
DOI: 10.1002/(sici)1096-8628(19990205)88:1<29::aid-ajmg5>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Marker-to-marker linkage disequilibrium on chromosomes 5q, 6p, and 8p in Irish high-density schizophrenia pedigrees

Abstract: Linkage disequilibrium (LD) is a potentially powerful tool for the localization of disease genes for complex disorders. Most prior studies of the relationship between genetic distance and LD have examined only very short distances, focusing on the role of LD in fine-mapping and positional cloning. We examine here the relationship between marker-to-marker (M-M) LD and somewhat greater genetic distances. We analyzed 622 M-M pairings on chromosomes 6p, 8p, and 5q in 265 native Irish pedigrees ascertained for a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…102,103 However, a published study has not been able to find significant evidence for linkage on 8p region. 104 It is important to take into consideration that Kendler et al 105 found an association between 8p22-21 locus and some clinical features in 265 multiplex schizophrenia pedigrees. More specifically, affected individuals from families with evidence of linkage to 8p had significantly more affective deterioration and thought disorders, a worse outcome, and fewer depressive symptoms than affected individuals from the other families in the study.…”
Section: Chromosome 8p Neuropsychiatric Disorders and Cancermentioning
confidence: 82%
“…102,103 However, a published study has not been able to find significant evidence for linkage on 8p region. 104 It is important to take into consideration that Kendler et al 105 found an association between 8p22-21 locus and some clinical features in 265 multiplex schizophrenia pedigrees. More specifically, affected individuals from families with evidence of linkage to 8p had significantly more affective deterioration and thought disorders, a worse outcome, and fewer depressive symptoms than affected individuals from the other families in the study.…”
Section: Chromosome 8p Neuropsychiatric Disorders and Cancermentioning
confidence: 82%
“…16 In addition, although Ireland is not a genetic isolate, the degree of genetic variation in Ireland is substantially less than in a general US sample. 17 The current Irish population derives largely from a series of prehistoric Celtic invasions, supplemented in the last 400 years by English and Scottish settlement.…”
Section: Introductionmentioning
confidence: 96%
“…In the Irish context, marker-to-marker analysis of association conducted between adjacent microsatellite markers on chromosome 5, 6 and 8 showed significant association for 96% of all markers within 0.5 cM of each other, 67% within 0.5-1 cM, 35% within 1-2 cM, 15% within 2-4 cM, 8% within 5-10 cM and 7% over 10 cM. 15 This suggests that this population may have certain advantages in a positional cloning experiment. However, extensive LD would be a disadvantage for fine mapping of association, for example, at candidate gene loci.…”
Section: Introductionmentioning
confidence: 97%